The depression of sphalerite during carbon pre-flotation and lead flotation at the Century Mine concentrator - Healy, Daniel Francis (Curtin University, 2005)
The differential lead-zinc flotation process has been practised since 1912, yet selectivity in the process remains a significant technical issue in many operations. The minerals processing operation at Zinifex Limited's Century Mine, which uses differential flotation, began in November 1999 and the flotation behavior of the ore remains a major research interest. The present study was aimed to determine the possible mechanisms of sphalerite recovery during carbon pre-flotation and lead flotation in this operation including identification of the variables that affect these two flotation stages and also identify depressants for sphalerite that offer better selectivity during these stages. To achieve this aim, the study was undertaken in two stages: a review of literature related to selectivity during lead-zinc flotation, and an experimental program consisting of bench-scale flotation tests wherein the various experimental variables were systematically varied. A comparison between the data generated to those of the plant was also undertaken. The review of literature revealed four basic mechanisms of sphalerite recovery: activation of the sphalerite surface, composite particle flotation with galena and gangue, graphitic inclusions in the mineral surface and entrainment in the froth. The depression or rejection of sphalerite on the other hand could be affected by grinding, froth washing and the use of chemical depressants including cyanides, zinc sulfate, abraded iron and iron sulfate, sodium sulfide, sodium sulfite and metabisulfite, and organic depressants derived from selective collectors.The results from the experimental program indicate that: (a) activation of the sphalerite surface as a mechanism of sphalerite recovery during lead flotation was not significant at the Century Mine concentrator, (b) the recovery of sphalerite during the carbon pre-flotation was predominantly due to a bulk flotation action and entrainment in the froth, (c) composite particle recovery was a significant contributing factor in the recovery of sphalerite in lead flotation, and (d) mineral oxidation was only significant for galena and occurred mostly during pre-flotation, but the use of cyanide adequately counters any effect on sphalerite recovery. The investigation on the variables that affect the pre-flotation and lead flotation circuits revealed that: (a) reducing the pulp density and the amount of frother added during pre-flotation significantly reduced the bulk flotation action and entrainment of sphalerite in the froth, b) grinding the ore finer (P80 = 40 μm) reduced the recovery of sphalerite as composite particles during lead flotation, and (c) the pulp pH was best maintained at natural pH during pre-flotation and at an elevated alkaline pH (pH 9.5) during lead flotation for optimal selectivity. In terms of depressants it was found that zinc sulfate specifically depressed sphalerite during lead flotation.